Determining the Effects of Neddylation on Cullin‐RING Ligase–Dependent Protein Ubiquitination. Issue 3 (22nd March 2022) - Wang, Kankan; Liu, Xing
Abstract: As the largest family of ubiquitin (Ub) E3 ligases, cullin‐RING ligases (CRLs) play crucial roles in various cellular processes, and their activities are tightly regulated by orchestrated mechanisms. Neddylation, the conjugation of a Ub‐like protein NEDD8 to a target protein such as the cullin, represents a key regulatory mechanism for CRLs. Biochemical and structural studies of a few CRLs have revealed that cullin neddylation alters the CRL conformation and activates CRL‐dependent protein ubiquitination. Here, using CUL2‐RING ligase (CRL2) as an example, we describe our protocols for the preparation of recombinant CUL2 with or without NEDD8 conjugation, which is further used to quantitatively determine the effect of neddylation on CRL2‐dependent protein ubiquitination in vitro . © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Expression and purification of CUL2RBX1 from Escherichia coli Support Protocol : Further purification of CUL2RBX1 with additional chromatography on an FPLC system Basic Protocol 2 : Reconstitution of cullin neddylation for quantitative ubiquitination assay in vitro